The fly-away cottage and other stories - Blyton, Enid; Bradley, Maureen (Award Worksop, 1993)
The Fly-Away Cottage and Other Stories by Enid Blyton is a delightful collection of short stories that whisk young readers away to whimsical adventures in enchanting settings. The title story features a magical cottage that can soar into the sky, leading to a series of charming escapades filled with fun and friendship. Each tale is rich with imagination, introducing children to lovable characters and the excitement of exploring new worlds. With themes of wonder, camaraderie, and the joy of discovery, this collection showcases Blyton's engaging storytelling and is perfect for sparking the imagination of young readers.